Modifikasi Biodiesel Melalui Reaksi Oksidasi Menggunakan Gelombang Ultrasonik - Aisyah Aisyah; Sappewali Sappewali; Nurlina Nurlina (Al-Kimia, 2013)
Biodiesel is an alternative energy fuel that is sustainable and environmentally safe. However, biodiesel has a higher cloud point than fuel diesel because it contains several saturated fatty acids such as oleic acid, linoleic and linolenic acid so that biodiesel tend to solidify at a temperature higher than the freezing point of diesel. This study aims to modify biodiesel from candlenut oil (Aleurites moluccana) through oxidation reaction by KMnO4 using ultrasonic equipment. The products obtained were analyzed using FTIR and GCMS instrument. FTIR analysis showed that spectral data of the four modified samples which run in 20, 30, 40 and 50 minutes practically similar. The methyl ester products are characterized by typical bands at specific frequencies such as stretch of C = O; C-C; C-H (sp3) and = C-H (sp2). Fragmentation patterns by GCMS showed that the oxidation reaction in 20, 30, 40 and 50 minutes did not undergo bond disconnection. The components produced is methyl palmitate, methyl linoleate, methyl oleate, heksadekanoat acid, 9, 12 and 9,17oktadekadienal oktadekadienoat acid.